Comparison of clinicopathological features and prognostic analysis between early-onset and late-onset advanced rectal mucinous adenocarcinoma - Du Rui; Chang Yue; Li Yonghai; Cheng Yuanguang; Zhang Juan; Zhang Chengyue; Xu Liejuan; Liu Yuancheng (结直肠肛门外科)
[Objectives] To compare the clinicopathological features with early-onset and late-onset advanced rectal mucinous adenocarcinoma and analysis the prognosis. [Methods] This study collected patients with first diagnosed advanced rectal mucinous adenocarcinoma from 2010 to 2020 through the SEER database. According to the age at diagnosis, patients were divided into an early-onset group (age<50 years at diagnosis, totaling 155 cases) and a late-onset group (age ≥ 50 years at diagnosis, totaling 679 cases). The clinicopathological features of the two groups were compared, and survival analysis was performed. [Results] There were no significant differences in the proportions of patients of different genders, races, degrees of differentiation, T stages, preoperative CEA, perineural invasion, and tumor diameters between the two groups (P>0.05). Compared with the late-onset group, the early-onset group had lower patients proportions of divorce, separation, or widowhood (11.6% vs. 27.4%), 1-11 lymph node dissections (19.4% vs. 27.4%), and cancer nodule negativity (67.7% vs. 76.1%). However, the early-onset group had higher patients proportions of TNM stage Ⅲ (76.1% vs. 58.6%), N2 stage (33.5% vs. 18.1%), >20 lymph node dissections (29.7% vs. 19.9%), lymph node positivity (58.1% vs. 45.4%), receiving chemotherapy (93.5% vs. 78.8%), receiving radiotherapy (75.5% vs. 56.1%), and receiving full course systemic therapy (41.3% vs. 21.2%) (P<0.05). The longest follow-up time for both groups was 131 months. During the follow-up period, the overall survival rates of the early-onset and late-onset groups were 59.4% and 45.5%, and the 5-year survival rates were 66.1% and 57%, respectively. The average survival time of the early-onset group was 91.885 months, while the median survival time of the late-onset group was 76 months, with an average survival time of 78.348 months. Both Breslow test (Wilcoxon test) and Log-rank test results indicated that the survival rate of the early-onset group was higher than that of the late-onset group (P<0.05). Cox proportional hazards regression model analysis was performed on 834 cases of advanced rectal mucinous adenocarcinoma, revealing that late-onset (age ≥ 50 years at diagnosis), male gender, unstable marital status (divorce, separation, widowhood, unmarried, or unknown), N2 stage, positive perineural invasion, tumor diameter>5 cm, no chemotherapy, preoperative + postoperative radiotherapy, and preoperative systemic therapy were independent risk factors for survival prognosis in advanced rectal mucinous adenocarcinoma. Cox proportional hazards regression model analysis was also performed on 155 cases of early-onset advanced rectal mucinous adenocarcinoma, showing that unmarried or unknown marital status and positive perineural invasion were independent risk factors for survival prognosis in early-onset advanced rectal mucinous adenocarcinoma. [Conclusion] The possibility of adverse prognostic factors is higher in early-onset advanced rectal mucinous adenocarcinoma, such as a higher proportion of stage Ⅲ and lymph node positivity, and a lower proportion of cancer nodule negativity. However, its long-term or short-term survival outcomes are superior to those of late-onset advanced rectal mucinous adenocarcinoma, which may be related to adequate lymph node dissection during surgery and chemotherapy receipt.